ENHANCING HUMAN FACTORS ENGINEERING (HFE) IN FRONT-END ENGINEERING DESIGN (FEED) THROUGH VALVE CRITICALITY ANALYSIS - Shafie, N. L.; Mohammad, R.; Venugopal, A.; Maarop, N.; Othman, N. (Journal of Engineering and Technology (JET), 2025)
Human Factors Engineering (HFE) is an interdisciplinary field that studies the interactions between humans, their tasks, and the broader organizational systems. Its goal is to improve both human performance and system efficiency. In the Front-End Engineering Design (FEED) phase, a critical challenge lies in designing and positioning key components like valves to ensure their functionality and ease of maintenance. Poor valve design and placement can result in safety hazards, inefficiencies, and increased operational risks. To address this issue, this paper explores the integration of Valve Criticality Analysis (VCA) within the HFE framework during the FEED stage. The approach involves classifying valves according to their criticality, evaluating their operational roles, and assessing the potential consequences of valve failures. This classification aids in making informed decisions about optimal valve design and placement. Findings from applying VCA during the FEED stage indicate that categorizing valves by their criticality enhances the identification of high-risk components, improves operational safety, and reduces human factor-related risks when introduced early in the design phase. This work presents a novel methodology that strengthens safety and operational effectiveness while offering a template for future projects.